Assessment of sex analysis in studies of technology-based interventions to alleviate caregiver burden among caregivers of persons with dementia. (May 2018) - Xiong, Chen; Mansfield, Elizabeth; Colantonio, Angela
Background: With an increase in the number of family caregivers for persons with dementia, caregiver burden is a major concern. Defined as computer-based devices and programs, technology has been identified as an intervention to address this issue. However, to date, there is little consideration of sex differences among caregivers in the design and planning of these interventions. Objective: To systematically review the literature on technology-based interventions for caregivers of persons with dementia and report the frequency and approaches of sex-based analysis. Methods: The literature was systematically searched for reviews of technology-based interventions for caregivers of persons with dementia. All titles and abstracts of publications included in the retrieved reviews were screened using pre-determined inclusion and exclusion criteria. Full text articles that met the inclusion criteria were included for analysis. Results: Four reviews were identified and 19 articles representing 17 studies were retrieved. Among these studies, only four examined outcomes by sex. In the studies that examined outcomes by sex, three reported significant differences ( p  < 0.05) between male and female caregivers. Conclusions: There is currently a lack of (1) sex-based analyses, (2) inclusion of males and (3) provision of sex-specific information in studies of technology-based interventions for caregivers of persons with dementia.